Kajian Historis Peran Perempuan Dalam Pelayanan di Tengah Tradisi Abad Satu - Tumiwa, Evi; Nesa, Nathania (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
The study explores the Historical role of women in service the first centur through a qualitative historical approach with a literature review. The findings show that various tradition in the first century limiting women’s rights and roles. However, historical and biblical research records reveal significant female figures who contributed to religious and social life. Women were actively involved in early Christian communities, played crucial roles in biblical narratives, participate in service. The study highlights the how important the presence of women, especially in service, half of various traditions that existed in the first century limiting women’s rights and roles. The research is giving women an understanding and realize that there are roles and responsibilities that must be carried out ini the midst of challenges that require women to continue to try and fight for their lives individually and with others.